2014
DOI: 10.1038/nchembio.1593
|View full text |Cite
|
Sign up to set email alerts
|

A new mechanism of allostery in a G protein–coupled receptor dimer

Abstract: SB269652 (1) is the first drug-like allosteric modulator of the dopamine D2 receptor (D2R), but contains structural features associated with orthosteric D2R antagonists. Using a functional complementation system to control the identity of individual protomers within a dimeric D2R complex, we converted the pharmacology of the interaction between SB269652 and dopamine from allosteric to competitive by impairing ligand binding to one of the protomers, indicating that the allostery requires D2R dimers. Additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
214
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(229 citation statements)
references
References 58 publications
14
214
1
Order By: Relevance
“…Until recently, examples of small molecule allosteric modulators were lacking for the D 2 R. We previously demonstrated that 1 bound the D 2 R in a bitopic mode and acted as a negative allosteric modulator of dopamine binding and function across a D 2 R dimer. 13 Studies at the mAChRs have used ligand fragmentation approaches to isolate orthosteric and allosteric pharmacophores from a bitopic ligand. 10,11 In this study we were able to isolate 3 an allosteric fragment of 1, derived from the indole-2-carboxamide moiety of the parent compound.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Until recently, examples of small molecule allosteric modulators were lacking for the D 2 R. We previously demonstrated that 1 bound the D 2 R in a bitopic mode and acted as a negative allosteric modulator of dopamine binding and function across a D 2 R dimer. 13 Studies at the mAChRs have used ligand fragmentation approaches to isolate orthosteric and allosteric pharmacophores from a bitopic ligand. 10,11 In this study we were able to isolate 3 an allosteric fragment of 1, derived from the indole-2-carboxamide moiety of the parent compound.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study identified two residues at the top of TM2 (Val91 2.61 and Glu95 2.65 ) that interact with the indole-2-carboxamide moiety of 1 and mutation of these residues to alanine reduced the affinity and/or negative cooperativity of 1 (Figure 5a, Table 2). 13 We hypothesised that if 3 occupies the same binding pocket as the 1H-indole-2-carboxamide moiety of 1, then one would expect a similar sensitivity to mutation of these residues. Mutation of Val91 2.61 Ala removed any effect of 3 up to a concentration of 300 µM upon a dopamine in a pERK1/2 assay, indicating this residue is key for 3 binding or function (Figure 5b, Table 2).…”
Section: Pharmacologymentioning
confidence: 99%
See 3 more Smart Citations